![\bf \begin{cases} \quad3x+2y=-9\\ -10x+5y=-5 \end{cases}](https://tex.z-dn.net/?f=%5Cbf%20%5Cbegin%7Bcases%7D%0A%5Cquad3x%2B2y%3D-9%5C%5C%0A-10x%2B5y%3D-5%0A%5Cend%7Bcases%7D)
so hmm the idea behind the elimination, is to make the value atop or below, of either variable, the same but with a negative sign
so hmmm say... we'll eliminate "y"
so... let's see, we have 2y and 5y, both positive
what do we multiply 2y to get a negative -5y, that way, -5y +5y = 0 and poof it goes
well let's see, let's try "k"
![\bf 2yk=-5y\implies k=-\cfrac{5y}{2y}\implies k=-\cfrac{5}{2}](https://tex.z-dn.net/?f=%5Cbf%202yk%3D-5y%5Cimplies%20k%3D-%5Ccfrac%7B5y%7D%7B2y%7D%5Cimplies%20k%3D-%5Ccfrac%7B5%7D%7B2%7D)
so.. if we multiply 2y by -5/2, we'll end up with -5y
well, let's multiply that first equation then by -5/2
![\bf \begin{array}{rllll} 3x+2y=-9&\qquad\times -\frac{5}{2}\implies &-\frac{15}{2}x-5y=\frac{45}{2}\\\\ -10x+5y=-5&\implies &-10x+5y=-5\\ &&---------\\ &&\frac{-35}{2}x+0\quad=\frac{35}{2} \end{array}\\\\ -----------------------------\\\\ \cfrac{-35}{2}x=\cfrac{-35}{2}\implies \cfrac{-35x}{2}=\cfrac{-35}{2}\implies x=\cfrac{2}{-35}\cdot \cfrac{-35}{2} \\\\\\ \boxed{x=1}](https://tex.z-dn.net/?f=%5Cbf%20%5Cbegin%7Barray%7D%7Brllll%7D%0A3x%2B2y%3D-9%26%5Cqquad%5Ctimes%20-%5Cfrac%7B5%7D%7B2%7D%5Cimplies%20%26-%5Cfrac%7B15%7D%7B2%7Dx-5y%3D%5Cfrac%7B45%7D%7B2%7D%5C%5C%5C%5C%0A-10x%2B5y%3D-5%26%5Cimplies%20%26-10x%2B5y%3D-5%5C%5C%0A%26%26---------%5C%5C%0A%26%26%5Cfrac%7B-35%7D%7B2%7Dx%2B0%5Cquad%3D%5Cfrac%7B35%7D%7B2%7D%0A%5Cend%7Barray%7D%5C%5C%5C%5C%0A-----------------------------%5C%5C%5C%5C%0A%5Ccfrac%7B-35%7D%7B2%7Dx%3D%5Ccfrac%7B-35%7D%7B2%7D%5Cimplies%20%5Ccfrac%7B-35x%7D%7B2%7D%3D%5Ccfrac%7B-35%7D%7B2%7D%5Cimplies%20x%3D%5Ccfrac%7B2%7D%7B-35%7D%5Ccdot%20%5Ccfrac%7B-35%7D%7B2%7D%0A%5C%5C%5C%5C%5C%5C%0A%5Cboxed%7Bx%3D1%7D)
so.. now we know x = 1.... so let's plug that in say hmmm 2nd equation